The Effect of Eruca sativa extract on Gram Posative and Negative Bacteria (Baghdad Science Journal, 2007)
The antibacterial effect of (Eruca sativa) extract was evaluated by an in vitro study testing the growth of various Gram-Positive and Gram-Negative bacteria . The bactericidal activity of this extract was analyzed by serial dilution in tubes. This study,found that Gram-Negative and Gram-Positive bacteria susceptible to very low eruca concentrations. On the other hand, Gram-positive bacteria were more susceptible than Gram-negative bacteria, the minimal bactericidal concentration of Gram-positive bacteria was 5 mg ml-1 but minimal bactericidal concentration of Gram-negative bacteria was 10 mg ml-1 that mean duble inhibation concentration of Gram-positive bacteria . this study suggest that Eruca sativa leaves have inhibation effect on Gram-Posative and Gram-Negative bacteria and Eruca sativa was natural material with little side effect.